PARTISIPASI MASYARAKAT PETANI DALAM REVITALISASI SISTEM PERTANIAN TERPADU (Studi Kasus di desa Timbang Lawan Kecamatan Bahorok Kabupaten Langkat) - Putra Solihin (Perspektif Sosiologi, 2012)
Abstract:. Revitalization of integrated farming emerged as agriculture should be developed and maintained for future generations functioned turns over to oil palm plantations. This condition is make to the income derived from agriculture is not comparable to the revenue of oil palm plantations. The development of oil palm plantations make Timbang Lawan village which was formerly a rice barn in a rural area that is not seeded anymore agriculture. This makes the government especially the village government to revitalize agriculture in a way that integrated farming Timbang Lawan Village against a back in the area. Integrated farming is done so that farmers can take advantage besides rice, farmers can also use vegetables for sale as integrated farming makes the soil planted with rice and various kinds of vegetables. Method research is to study the case study method with a combination of qualitative and quantitative approaches. Input was collected by observation, in-depth interviews, questionnaires and literature study. As the unit of analysis, as well as samples of informants in this study were farmers Bahorok Timbang Lawan village Langkat district. Interpretation and analysis of input is done using the input obtained from the observations, interviews, and questionnaires were interpreted and analyzed based support literature that can be taken an integrated farming system conclusion. Program Timbang Lawan village has increased farmers' self-reliance in all aspects of so as to improve food security in the Timbang Lawan village and agricultural production has a high selling.   Keyword: participation, farmer community, revitalize, system of integrated                                   agricultural